Jose Rizal and the Birth of the Social Sciences in the Philippines - Mojares, Resil B. (Archīum Ateneo, 2024)
The paper narrates jose Rizal’s sojourn in Berlin in 1887 as a defining moment in the emergence of the social sciences as a Filipino discipline. it situates this moment in a much wider history, in which such factors as the expansion of the economy, civil bureaucracy, education, and nationalism gave rise to the first Filipino writings in such fields as history, anthropology, sociology, economics, and political science. in recalling Rizal and his time, the paper argues that there is a longer history of the disciplines in the Philippines than is usually acknowledged.